The Constitutionality of E-Voting in the Transformation of Digital Democracy: A Normative Analysis and Implications for Electoral Legitimacy - Arifin, Firdaus; Maarif, Ihsanul; Suryana, Cece; Permana, Fikri Chandra; Murbani, Anastasia Wahyu (Universitas Negeri Semarang, 2025)
Digital technology has changed many parts of life, including how democracies and elections work. Electronic voting, or E-Voting, is a new idea that could make elections better and more open for everyone. But Indonesia still has big problems with putting it into practice. These problems involve legal issues, technical difficulties, and whether people trust elections that use technology. This study looks at if E-Voting fits Indonesia's constitution, what the main problems are, and what other countries do that Indonesia could use. This research uses legal analysis, comparing different systems, and looking at ideas about democratic rules. The results show that Indonesia does not have clear rules for digital elections. This causes problems with legal certainty and could lead to arguments about election results. Also, online security risks and differences in how well people understand technology are important things that could affect how well E-Voting works. The study also found that countries like Estonia, Switzerland, and Brazil have used E-Voting well. They did this by using strong digital checks, strict rules, and independent groups to watch over the process. This study suggests that E-Voting could make Indonesia's democracy more modern. However, it must be put in place slowly, with good rules, and with programs to teach people about digital technology. So, changing laws, making online security better, and teaching voters are important steps. These steps will help make sure that changing to digital elections supports democratic ideas, fair elections, and the power of the people.